Challenges Of Grammar Translation Method: A Perception Of Novice English Language Teachers Of Secondary Level At Swabi (Journal of Namibian Studies : History Politics Culture, 2023)
This paper investigates the perception and attitude of novice EL teachers towards the Grammar Translation Method (GTM) in comparison to the Direct Method (DM). English language teaching (ELT) has become a central focus of educationists as English language received the status of international language and regarded English, a symbol of advancement in Pakistan. Language teaching needs a separate skill set and expertise to produce successful language learners. ELT uses different teaching methodologies for its learners; the most widely used among them are the Grammar Translation Method (GTM) and the Direct Method (DM). GTM focuses on linguistic competence while DM focuses on linguistic performance, both use different pedagogical techniques with each’s own pros and cons. Currently, the direct method is mostly employed in universities for language learning purposes while the majority of the secondary schools of Swabi use GTM traditionally. The novice EL teachers who have been exposed to the Direct method for 4-6 years when getting into the school for English language teaching face problems in pursuing their classrooms in GTM. The results contribute the lexical and contextual meaning which make a measurable contribution in the field of English language teaching (ELT) and literature. There is also room for the future researchers to conduct research in the field of other aspects and expand the analysis to its various types in the field of linguistics as well.